Internal Quality Management Model in Islamic Boarding School-Based Madrasah - Frandani, Muhammad; Tamam, Abas Mansur; Ahmad, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research aims to (1) analyze the need for an internal quality management model and (2) design an internal quality management model in Islamic boarding school-based madrasas. This research uses the Research and Development (R&D) method using ADDIE (Analysis, Design, Develop, Implement, Evaluate) procedures and steps. The research results show that the Pesantren-Based Madrasah Quality Assurance Team must receive full support from the Islamic boarding school leadership. The Ministry of Religion's version of the Madrasah Self-Evaluation Instrument (EDM) must be developed to accommodate educational evaluations in Islamic boarding schools. Islamic boarding school-based madrasa's internal quality management model consists of four stages. First, the planning stage which consists of (1) mission alignment, (2) SWOT analysis, (3) EDM gap analysis, and (4) preparation of a quality plan. Second, the quality fulfillment stage consists of (1) determining the person responsible for the program, (2) funding allocation, and (3) reporting on quality implementation. Third, the quality evaluation stage consists of (1) formative evaluation, (2) summative evaluation, (3) preparation of evaluation instruments, (4) data collection, and (5) analysis and preparation of recommendations. Fourth is the quality follow-up stage, which consists of (1) follow-up improvement and (2) follow-up standardization of changes.